Microbiologically proven case of primary breast tuberculosis (Indian Journal of Case Reports, 2020)
Tuberculosis (TB) of the breast is an uncommon presentation of extrapulmonary TB, it is uncommon even in countries where the incidence of pulmonary and extrapulmonary TB is high and its diagnosis is challenging due to non-specific clinical and imaging findings and often misdiagnosed as abscess or carcinoma. It is mainly diagnosed on the basis of histopathological examination. We have reported a case of primary TB of breast diagnosed by microbiological investigations. A 19-year-old female presented with a painful lump in the breast for the past 3 months. Primary breast TB was diagnosed by sample collect by fine-needle aspiration cytology, wherein Ziehl–Neelsen stain for acid-fast bacilli and cartridge-based nucleic acid amplification test were positive. The patient received antitubercular drugs and at 4 months follow-up, the swelling had resolved and the patient was asymptomatic.